Faktor-Faktor Yang Memengaruhi Harga Saham (Studi Empiris Pada Perusahaan Transportasi Yang Terdaftar Di Bursa Efek Indonesia) - Reni Dahar; Nino Sri Purnama Yanti; Fitria Rahmi (Jurnal Ekonomi dan Bisnis Dharma Andalas, 2020)
ABSTRACT This research is an empirical study conducted to analyze the influence of factors that influence the price of transportation company shares listed on the Indonesia Stock Exchange (IDX) from 2015-2018. These factors consist of microeconomic factors that are seen from the company's financial performance, namely the financial ratio of Earnings Per Share (EPS), Debt to Equity Ratio (DER), Return On Equity (ROE), Price to Book Value (PBV), and Dividend Payout ratio (DPR). The population is the transportation companies listed on the Indonesia Stock Exchange from 2015 to 2018, amounting to 27 companies. The sampling technique of this study was carried out using purposive sampling technique. The analytical method used to test the hypotheses in this study is multiple regression. Testing these data using STATA software and Microsoft Excel. The results of this study are Earnings Per Share (EPS) affect stock prices, Debt to Equity Ratio (DER), Return On Equity (ROE), Price to Book Value (PBV), and Dividend Payout ratio (DPR) have no effect on stock prices . EPS, DER, ROE, PBV and DPR have a simultaneous and significant effect on the stock prices of Transportation Sub Sector companies listed on the Indonesian Foam Exchange (BEI) from 2015 to 2018. ABSTRAK Penelitian ini merupakan studi empiris yang dilakukan untuk menganalisis pengaruh faktor-faktor yang memengaruhi harga saham perusahaan transportasi yang terdaftar di Bursa Efek Indonesia (BEI) dari tahun 2015-2018. Faktor tersebut terdiri dari faktor mikro ekonomi yang dilihat dari kinerja keuangan perusahaan yaitu rasio keuangan Earnings Per Share (EPS), Debt to Equity Ratio (DER), Return On Equity (ROE), Price to Book Value (PBV), dan Dividend Payout ratio (DPR). Populasinya yaitu perusahaan Transportasi yang terdaftar di Bursa Efek Indonesia tahun 2015 sampai dengan 2018 yang berjumlah 27 perusahaan. Teknik pengambilan sampel teknik purposive sampling. Metode analisis yang digunakan regresi berganda. Pengujian data-data tersebut menggunakan perangkat lunak STATA dan microsoft excel. Hasil penelitian ini adalah Earnings Per Share (EPS) berpengaruh terhadap harga saham, Debt to Equity Ratio (DER), Return On Equity (ROE), Price to Book Value (PBV), dan Dividend Payout ratio (DPR) tidak berpengaruh terhadap harga saham. EPS, DER, ROE, PBV dan DPR berpengaruh simultan dan signifikan terhadap harga saham perusahaan Sub Sektor Transportasi yang terdaftar di Busa Efek Indonesia (BEI) tahun 2015 sampai dengan 2018.